Specific Properties of Novel Two-Dimensional Square Honeycomb Composite Structures - M. R. M., Rejab; W. A. W., Hassan; J. P., Siregar; Bachtiar, Dandi (Trans Tech Publications Inc., 2014)
Hexagonal honeycomb cores have found extensive applications particularly in the aerospace and naval industries. In view of the recent interest in novel strong and lightweight core architectures, square honeycomb cores were manufactured and tested under uniform lateral compression. A slotting technique has been used to manufacture the square honeycomb cores based on three different materials; glass fibre-reinforced plastic (GFRP), carbon fibre-reinforced plastic (CFRP) and self-reinforced polypropylene (SRPP). As semi-rigid polyvinyl chloride (PVC) foam was placed in each of unit cells to further stiffen the core structure. The core then was bonded to two skins to form a sandwich structure. The compressive responses of the sandwich structures were measured as a function of relative density. In this paper, particular focus is placed on examining the compression strength and energy absorption characteristics of the square honeycombs with and without the additional foam core. Comparisons in terms of specific strength and specific energy absorption have shown that the CFRP core offers excellent properties. The presence of the foam core significantly increases the energy absorption capability of overall structure and the SRPP core could potentially be used as an alternative lightweight core material in recyclable sandwich structures.